1989
DOI: 10.1046/j.1468-2982.1989.0902091.x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Headache in the Male: Sex Steroid Pattern and Gonadotropic Response to Luteinizing Hormone Releasing Hormone

Abstract: Serum testosterone, dihydrotestosterone, delta 4-androstendione and 17 beta-estradiol, sex hormone binding globulin (SHBG) and gonadotropic response to luteinizing hormone releasing hormone (LHRH) were studied in 34 male subjects with episodic or chronic cluster headache (CH). The sex steroid free fractions and those bound to SHBG and albumin were determined by a simulatory computerized method based on the mass action law. Individual steroid values were dispersed over a wide range in CH patients. Total, free a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…With reference to the population of patients presented here, low testosterone levels have been noted previously in patients with episodic and chronic cluster headaches 17–19,23 . Three of the 10 chronic cluster patients in Nelson's studies had low testosterone levels which he attributed to opioid analgesic use 18 .…”
Section: Commentssupporting
confidence: 61%
“…With reference to the population of patients presented here, low testosterone levels have been noted previously in patients with episodic and chronic cluster headaches 17–19,23 . Three of the 10 chronic cluster patients in Nelson's studies had low testosterone levels which he attributed to opioid analgesic use 18 .…”
Section: Commentssupporting
confidence: 61%
“…Low testosterone levels had been noted previously in patients with episodic and chronic cluster headaches as much as three decades ago [23][24][25][26]. Three of the 10 chronic cluster patients in the study by Nelson [24] had low testosterone levels, which he attributed to opioid analgesic use.…”
Section: Testosterone Masculinization and Cluster Headachesmentioning
confidence: 67%
“…In accordance with the above, a study by Murialdo et al [26] looked at testosterone, its metabolites, 17β-estradiol, follicle-stimulating hormone (FSH), luteinizing hormone (LH), and luteinizing hormone-releasing hormone (LHRH) in patients with episodic cluster headache, chronic cluster headache, and healthy control subjects and found decreased total and free testosterone in chronic cluster headache sufferers only. In addition, LH peaks were lower in response to LHRH in this population, suggesting impairment in the pituitary-gonadal feedback loop.…”
Section: Testosterone Masculinization and Cluster Headachesmentioning
confidence: 75%
“…One study indicated differences between controls and patients in luteinizing hormone and follicle stimulating hormone levels. 5 Another study revealed monoaminergic dysfunction at the hypothalamic level in subjects with cluster headache. 6 It is possible that similar neuroendocrine differences exist both in the women described in the current study, and in patients with typical cluster headaches.…”
Section: Commentsmentioning
confidence: 99%